Analisis Marketing Mix 4P dalam Perspektif Islam : Studi Kasus Butik Omyka Collection - Nindya Ferdian Sari (Inspirasi Nusantara, 2022)
Business activity or business is an activity to meet the needs and desires of humans, organizations, and society at large. To meet the needs and desires of consumers while increasing product sales, companies need an integrated marketing concept called the marketing mix. The research method used is descriptive qualitative method. The data collection techniques used in the study were interviews and documentation. The object of research is Omyka Collection as the primary data source. Based on the results and discussions that have been found by researchers, researchers can conclude that the marketing mix strategy implemented by Omyka Collection in Sidoarjo City can be concluded that the products sold are always updated and designed according to market segmentation. Furthermore, in terms of the price set according to the quality of the material, the better the material, the higher the price offered. In the aspect of place or distribution in marketing their products, they prioritize locations or places that are strategic and easily accessible to consumers. Then in terms of promotions that have been done as much as possible by utilizing social media Instagram and shopee in marketing their products.